Objective Factors Affecting Uzbekistan's Access To The Bologna Agreement - Tursunoy Abduvokhid kizi Abdurakhimova (Zien Journals, 2024)
This article describes the author's scientific research about the efforts being made to join the Bologna process in the higher education system of our country, their rise to the level of state policy, and the achievements and shortcomings in this regard
Keywords: Lisbon Convention; ratification; transformation; credit module system